Factors affecting consumers’ green product purchase intentions among employees in Majlis Perbandaran Jasin / Liyana Sorfina Azmi - Azmi, Liyana Sorfina (Faculty of Business Management, 2017)
The current rapid growth in the economy and the patterns of consumers’ consumption and behaviour worldwide are the main cause of environmental deterioration. As the environment continues to worsen, it has become a persistent public concern in the developed countries and has recently awakens developing countries to the green movement. Inadequate information related to local and international marketers to understand consumer behaviour to develop a comprehensive distribution and marketing strategies of green products in the country where the trend is still new. Thus, this research aims to study the adoption of green purchase intentions among employees in Majlis Perbandaran Jasin in particular. The drivers of the adoption of green purchase intentions are subjective norms, attitude towards environment and green experience. There are 3 hypotheses constructed in this research. 100 self-administered questionnaires were distributed to the unit of analysis which is the employees of Majlis Perbandaran Jasin. The data collected were analysed using the Statistical Package for Social Science (SPSS). Results from this study show that attitude towards environment and green experience has significant impact on green purchase intentions. Recommendation for future research has also been included.